Peran Guru Bahasa Indonesia pada Pembelajaran Daring dalam Meningkatkan Keterampilan Berbahasa Siswa Kelas 1 MI Miftakhul Athfal Tembok Kidul - Lyswidia Andriarsih; Aprillia Dwi Salima (La-Tahzan: Jurnal Pendidikan Islam, 2022)
The Covid-19 pandemic that broke out in Indonesia, made the government take a number of policies in various fields. Including the education sector, the learning system that was previously face-to-face had to be changed to distance learning (PJJ) or online from home. The decision is certainly very influential on all parties involved in it (educational institutions, teachers, students, and parents), especially teachers who are the benchmark for student success. Teachers must carry out their role as much as possible so that learning objectives can be achieved well even in emergency conditions. The purpose of this study is to determine and understand the role of the teacher in the implementation of online learning, as well as its effect on improving students' language skills in grade 1 MI Miftakhul Athfal Tembok Kidul. This research is a descriptive quantitative research. Data analysis is done through data reduction, data display, conclusions and verification. For data collection techniques using observation, interviews, and documentation. From the data obtained, the researcher makes a conclusion which is presented in the form of a narrative. The results showed that the role of teachers in the online learning process in Indonesian language subjects at MI Miftakhul Athfal Tembok Kidul, all teachers used an online learning model, namely the WhatsApp application for class 1 (low grade) as a learning medium. In carrying out their role, teachers make learning tools in the form of lesson plans, share material in the WA group, provide assignments and evaluations. Teachers also focus on achieving reading and writing materials, by assigning students at each meeting to write and read the results of which are collected via WA in the form of photo and video files. Judging from the Indonesian language scores of grade 1 students, almost all of them are able to follow the learning well.